Church and State in Western Australia: Implementing New Imperial Paradigms in the Swan River Colony, 1827–1857 - Strong, Rowan (The journal of ecclesiastical history, 2010)
This article examines, through the work and attitudes of its first four governors, the relations between Church and State in the last Australia colony to be established. It covers the period from the foundation of the colony in 1829 to the arrival of the first resident bishop of Perth in 1857. It challenges the prevailing historiography of a colonial administration wedded to Anglican privilege, and discusses the persistence of an erastian mind-set among the colonial governors in the 1840s despite the advent of a new paradigm of autonomous imperial engagement by the Church of England.